PENGARUH PENERIMAAN TEKNOLOGI DENGAN METODE UTAUT TERHADAP MINAT MENGGUNAKAN MOBILE BANKING DI BSI TANGERANG - Alim, Muhammad Nurul; Hidayat, Wahyu; Amalia, Risqi (Islamic Banking & Economic Law Studies (I-BEST), 2024)
The purpose of this study is to determine the effect of UTAUT factors, namely Performance Expectations, Effort Expectations, Social Influence and Facilitating Conditions partially and simultaneously on customer interest in using BSI mobile banking services in Tangerang. With four independent variables, namely: Performance Expectations (X1), Business Expectations (X2), Social Influence (X3), and Facilitating Conditions and the dependent variable is Interest (Y). The population in this study were Bank Syariah Indonesia customers with a sample size of 110 respondents. This study applies quantitative research methods. The analysis used in this study is the measurement model test (outer model) and the structural model test (inner model). This study uses the SmartPLS 3.0 program to process data.The results of this study indicate that the Performance Expectation variable (X1) has a positive and significant effect on the variable customer interest in using mbanking services with a significance level of 0.000 <0.05. The Effort Expectation variable (X2) has a negative and insignificant effect on interest in using mbanking services with a significance level of 0.557>0.05. The Social Influence variable has a positive and significant effect on interest in using mbanking services with a significance level of 0.000 <0.05. Facilitating Conditions have a positive and insignificant effect on customer interest in using mbanking services with a significance level of 0.315>0.05 then simultaneously together the independent variables simultaneously affect the dependent variable interest in using mbanking services.This research is expected to be useful for further research that wants to develop further research knowledge, banking and academic parties.